Variation assessment of deformable registration in stereotactic radiosurgery. Issue 1 (February 2018) - Chang, C.-S.; Shih, R.; Hwang, J.-M.; Chuang, K.-S.
Abstract: Introduction: The regular functions of CT-MRI registration include delineation of targets and organs-at-risk (OARs) in radiosurgery planning. The question of whether deformable image registration (DIR) could be applied to stereotactic radiosurgery (SRS) in its place remains a subject of debate. Methods: This study collected data regarding 16 patients who had undergone single-fraction SRS treatment. All lesions were located close to the brainstem. CT and MRI two image sets were registered by both rigid image registration (RIR) and DIR algorithms. The contours of the OARs were drawn individually on the rigid and deformable CT-MRI image sets by qualified radiation oncologists and dosimetrists. The evaluation metrics included volume overlapping (VO), Dice similarity coefficient (DSC), and dose. The modified demons deformable algorithm (VARIAN SmartAdapt) was used for evaluation in this study. Results: The mean range of VO for OARs was 0.84 ± 0.08, and DSC was 0.82 ± 0.07. The maximum average volume difference was at normal brain (17.18 ± 14.48 cm 3 ) and the second highest was at brainstem (2.26 cm 3  ± 1.18). Pearson correlation testing showed that all DIRs' OAR volumes were linearly and significantly correlated with RIRs' volume (0.679–0.992, two tailed, P  << 0.001). The 100% dose was prescribed at gross tumor volume (GTV). The average maximum percent dose difference was observed in brainstem (26.54% ± 27.027), and the average mean dose difference has found at same organ (1.6% ± 1.66). Conclusion: The change in image-registration method definitely produces dose variance, and is significantly more what depending on the target location. The volume size of OARs, however, was not statistical significantly correlated with dose variance. Highlights: All DIR volumes of OARs were significantly and linearly correlated with RIR's. Lowest values of metrics in chiasm and highest values in normal brain. Dose variation correlated with OARs that sensitive with distance to target in DIR. Volume size of OARs did not significantly vary with dose variance.